2017
DOI: 10.1371/journal.pone.0175288
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor screening to identify women requiring oral glucose tolerance testing to diagnose gestational diabetes: A systematic review and meta-analysis and analysis of two pregnancy cohorts

Abstract: BackgroundEasily identifiable risk factors including: obesity and ethnicity at high risk of diabetes are commonly used to indicate which women should be offered the oral glucose tolerance test (OGTT) to diagnose gestational diabetes (GDM). Evidence regarding these risk factors is limited however. We conducted a systematic review (SR) and meta-analysis and individual participant data (IPD) analysis to evaluate the performance of risk factors in identifying women with GDM.MethodsWe searched MEDLINE, Medline in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 49 publications
3
71
1
7
Order By: Relevance
“…The performance of risk predictors was evaluated in terms of sensitivity (Sens), specificity (Sp), positive and negative predictive values (PPV and NPV, respectively), accuracy, and positive and negative likelihood ratios (PLR and NLR, respectively) with their odds ratio (OR) and 95% CI. Performance analysis also included the assessment of falsepositive results, defined by the formula 1-Sp 16,17,33,34 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of risk predictors was evaluated in terms of sensitivity (Sens), specificity (Sp), positive and negative predictive values (PPV and NPV, respectively), accuracy, and positive and negative likelihood ratios (PLR and NLR, respectively) with their odds ratio (OR) and 95% CI. Performance analysis also included the assessment of falsepositive results, defined by the formula 1-Sp 16,17,33,34 .…”
Section: Resultsmentioning
confidence: 99%
“…Also in agreement with other reports, we observed that the higher Sp shown by FG, HbA1c and HOMA-IR indicate them as the best predictors for ruling out GDM risk and the need for a diagnostic test 10,13,42,44,45 . universal screening are not available 16,17,46 . Therefore, the literature seems to support our results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vår studie viste økt prevalens av svangerskapsdiabetes i samsvar med nasjonale tall samt internasjonale rapporter (2). Prevalens av svangerskapsdiabetes varierer med etnisitet (13), og ulike studier bruker forskjellige risikofaktorer som grunnlag for å identifisere kvinner med økt risiko for svangerskapsdiabetes, noe som gjør sammenlikning utfordrende (14). Tall fra Medisinsk fødselsregister viste fylkesvise forskjeller i prevalens fra 2,8 % til 11 % i 2017 (1).…”
Section: Diskusjonunclassified
“…[7,11]. В то же время многочис-ленные исследования показали, что риск ГСД имеется у женщин, страдающих ожирением [12,13], метаболическим синдромом [14,15], поликистозом яичников, эндометриозом [16], а также у имеющих в анамнезе гормональные причины невынашивания беременности [17], осложнение ГСД предыдущей беременности [7,10,18]. Результаты наших исследований вы-явили заболевания трех и более функциональ-ных систем (эндокринной, сердечно-сосуди-стой, иммунной, желудочно-кишечного тракта) у 85 % матерей, беременность у которых ослож-нилась гестационным диабетом.…”
unclassified